Réponses

2014-03-29T13:35:56+01:00
1. a) 1/3 + 5/9                    2. a) 2/3 + 1/8                      3. tu multiplie juste les deux
    = 3/9+5/9                              = 16/24 + 3/24                  nombres du hauts et les 
    = 8/9                                    = 19/24                             deux nombres du bas, et
                                                                                        tu la réduis si tu peux.
b) 11/6 + -7/3                         b) -2/5 + 3/4
    = 11/6 + -14/6                        = -8/20 + 15/20             4. a) 4/5 : 3/7
    = -3/6                                    = 7/20                                 = 4/5 * 7/3
                                                                                           = 28/15
c) 17/24 - -5/6                         c) -5/7 - 3/2
    = 17/24 - -20/24                      = -10/14 - 21/14                b) 8/5 : 7/3
    = 37/24                                  = -31/14                               = 8/5 * 3/7
                                                                                            = 24/35
                                              d) 4/7 - 4/5
                                                  = 20/35 - 28/35                 c) 2/-7 : 1/5
                                                  = -8/35                                = 2/-7 * 5/1
                                                                                            = 10/-7
                                               e) 3 - 5/7
                                                   = 21/7 - 5/7                      d) -5/4 : 3
                                                   = 16/7                                 = -5/3 * 1/3
                                                                                             = -5/9
                                                 f) -2 - 3/4
                                                    = -8/4 - 3/4                      e) 1 : (-1/4)
                                                    = -11/4                                = 1/1 * 4/-1
                                                                                               = 4/-1
                                                                                                                                                                                                                       f)  (-1) : (-8)
                                                                                               = (-1/1) * (1/-8)
                                                                                               = -1/-8